2005
DOI: 10.1002/bio.813
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the fluorescence behaviour of carbazole derivatization reagents

Abstract: The carbazole ring is the basic structure present in the fluorescence derivatization reagents 9-chlorocarbonylcarbazole and 9-carbazolylacetic acid. The fluorescence behaviour of these carbazole derivatives was studied in solvents with different polarities (cyclohexane, ethanol, acetonitrile, water) and at different pH values (4.5 and 8.8). The influence of the low polarity environment afforded by 2-hydroxypropyl-beta-cyclodextrin (HPbeta-CD) is also described. The behaviour of the fluorescent reagents is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Characteristically these compounds show absorbance in the range from 250 to 400 nm. In the case of U1, the fluorescence emission spectrum is broad and positioned in the blue-green range with maxima at 475 nm and 500 nm, which is characteristic for carbazole moieties [25]. All the photophysical properties of all tested biosensors are gathered in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristically these compounds show absorbance in the range from 250 to 400 nm. In the case of U1, the fluorescence emission spectrum is broad and positioned in the blue-green range with maxima at 475 nm and 500 nm, which is characteristic for carbazole moieties [25]. All the photophysical properties of all tested biosensors are gathered in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the chemosensor fluorescence decays upon addition of the various drug concentrations revealed no change in the lifetime; however the time of measurment was elongated, indicating a loss of fluorescence intensity. This is clear evidence of the static character of the quenching, and the formation of stable complexes in the ground state [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Carbazole and its derivatives possess highly conjugated systems, engage in active ICT and are used as electron‐donating chromophores . Carbazole compounds are promising candidates for electroluminescent and photorefractive devices because of their electron‐donating and hole‐transporting properties, and their remarkable application as fluorescent sensors . In the bis‐azine type ligand, the electron density is located on the [C=N−N=C] moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61][62][63] Carbazole compounds are promising candidates for electroluminescent and photorefractive devices because of their electron-donating and hole-transporting properties, and their remarkable application as fluorescent sensors. [64][65][66][67][68][69][70][71][72][73][74][75][76] In the bis-azine type ligand, the electron density is located on the [C=N−N=C] moiety. Binding NMR, Nuclear magnetic resonance spectroscopy; PBS, Phosphate-buffered saline; TDDFT, Time-dependent density functional theory; UV, Ultraviolet; Vis, Visible of metal ions to the ligand affects the electron density and thus influences the fluorescence of the ligand.…”
mentioning
confidence: 99%
“…Previous studies have documented that BCyDs exhibit a spectral red shift, also referred as bathochromic shift, in fluorescence spectra. 21,22 A bathochromic spectral shift in the fluorescence emission spectra was noted when HPCyD was complexed with a carbazole derivative, 21 which bears slight structural similarity to ICG due to three benzene rings with nitrogen. Another study reported that upon encapsulation of fluorescent dye molecules, the hydrophobic cavity of cyclodextrins results in spectral red shifts of dye.…”
mentioning
confidence: 98%